2004
DOI: 10.2337/diabetes.53.11.2883
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Serum Lipids and Risk of Diabetic Macular Edema in Type 1 Diabetes

Abstract: We evaluated the relationships between serum lipid levels and clinically significant macular edema (CSME), hard exudates, and other diabetic retinopathy (DR) end points in a population with type 1 diabetes. We studied data from serum lipids that were measured annually among the 1,441 Diabetes Control and Complications Trial (DCCT) participants. We used proportional hazards regression models to examine the relationship of the cumulative average of lipid levels (total, LDL, and HDL cholesterol, total-to-HDL chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
2
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(128 citation statements)
references
References 43 publications
9
112
2
5
Order By: Relevance
“…In turn, lowered cholesterol and blood pressure levels might have contributed to the rescue of ocular structures. In fact, in patients from the DCCT cohort it was shown that higher serum lipids were associated with macular oedema and retinal hard exudates [31]. On the other hand, reducing blood pressure values can help regulate blood perfusion in the retinal vessels, thus decreasing shear stress and the consequent damage of the endothelial lining of the small vessels of the retina [1,32].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, lowered cholesterol and blood pressure levels might have contributed to the rescue of ocular structures. In fact, in patients from the DCCT cohort it was shown that higher serum lipids were associated with macular oedema and retinal hard exudates [31]. On the other hand, reducing blood pressure values can help regulate blood perfusion in the retinal vessels, thus decreasing shear stress and the consequent damage of the endothelial lining of the small vessels of the retina [1,32].…”
Section: Discussionmentioning
confidence: 99%
“…Other major systemic risk factors include hypertension, dyslipidaemia and high body mass index, although there is substantial variation in the consistency and strength of the association with these risk factors (Miljanovic et al. 2004; Ding & Wong 2012; Yau et al. 2012).…”
Section: Introductionmentioning
confidence: 99%
“…20 Besides, a high total to high-density lipoprotein (HDL) cholesterol ratio and elevated LDL cholesterol were each associated with the development of clinically significant macular oedema. 21 Furthermore, measurement of lipoprotein subclass using nuclear magnetic resonance showed positive associations between the severity of retinopathy and triglyceride levels, and LDL particle concentration and apolipoprotein B levels (a constituent lipoprotein of very-low density, intermediate-density lipoproteins, and LDL), and a negative association with HDL cholesterol. 22 …”
Section: Do Lipids Have a Role?mentioning
confidence: 99%